Overexpression of OsRRK1 Changes Leaf Morphology and Defense to Insect in Rice - Ma, Yinhua; Zhao, Yan; Shangguan, Xinxin; Shi, Shaojie; Zeng, Ya; Wu, Yan; Chen, Rongzhi; You, Aiqing; Zhu, Lili; Du, Bo; He, Guangcun (Frontiers in Plant Science, 2017)
It has been reported that the receptor-like cytoplasmic kinases (RLCKs) regulate many biological processes in plants, but only a few members have been functionally characterized. Here, we isolated a rice gene encoding AtRRK1 homology protein kinase, OsRRK1, which belongs to the RLCK VI subfamily. OsRRK1 transcript accumulated in many tissues at low to moderate levels and at high levels in leaves.. Over-expression of OsRRK1 (OE-OsRRK1) caused adaxial rolling and erect morphology of rice leaves. In the rolled leaves of OE-OsRRK1 plants, both the number and the size of the bulliform cells are decreased compared to the wild-type (WT) plants. Moreover, the height, tiller number and seed setting rate were reduced in OE-OsRRK1 plants. In addition, the brown planthopper (BPH), a devastating pest of rice, preferred to settle on WT plants than on the OE-OsRRK1 plants in a two-host choice test, indicating that OE-OsRRK1 conferred an antixenosis resistance to BPH. The analysis of transcriptome sequencing demonstrated that several receptor kinases and transcription factors were differentially expressed in OE-OsRRK1 plants and WT plants. These results indicated that OsRRK1 may play multiple roles in the development and defense of rice, which may facilitate the breeding of novel rice varieties.